Disruptive innovation for the base of the pyramid market – a case study on China's Shanzhai cell phone industry. (1st January 2012) - Zhou, Jianghua; Tong, Yunhuan; Li, Jizhen
This paper explores how firms can initiate disruptive innovation in the Base of the Pyramid (BoP) market. Based on the extant literatures on BoP and disruptive innovation, this paper adopts case study methodology and analyses the process of disruptive innovation of Shanzhai cell phone industry. Combining qualitative data with grounded theory, this paper finds that the structural disruption and the functional disruption of technology influence different factors of the business model of companies and the integration of disruptive technology with business model innovation is necessary for firms to initiate disruptive innovation. The companies with disruptive innovation can leverage the BoP-oriented small- and medium-sized enterprises and the existing industry system to fulfil the disruption process in the BoP market. The findings of this paper contribute to the research both on disruptive innovation and on BoP markets.